Classical simulation of coherent population return in coupled optical waveguides. Issue 8 (4th May 2022) - Naim, Nida; Deng, Li; Qian, Jun; Niu, Yueping; Gong, Shangqing
Abstract : An optical analog to coherent population return (CPR) is carried out in two evanescently coupled waveguides. Thepropagation constants of the two waveguides are different and the coupling between them is slowly varied for the adiabatic condition.The analog to the CPR corresponds to complete light return. Furthermore, we simulate two extensions of the CPR. One is that thecoupling is unchanged after it reaches its maximum, while the another one is that the coupling is replaced by a sudden decrease fromthe maximum to zero (half-CPR). We can both observe nearly 50:50 beam splitting in the two extensions. However, the half-CPRperforms better, which implies its application for achromatic beam splitters. Finally, we note that the waveguide structure proposedhere for beam splitters is simpler than those based on the stimulated Raman adiabatic passage and the rapid adiabatic passage.